1993
DOI: 10.1111/j.1469-8749.1993.tb11640.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐organic Falure to Thrive; Growth Failure Secondary to Feeding‐skills Disroder

Abstract: SUMMARY In this article the authors propose that non‐organic failure to thrive (FTT) is a growth failure secondary to feeding‐skills disorder, and that this disorder is neurophysiological in origin. The symptoms of feeding‐skills disorder were suggestive of an oral sensorimotor impairment which is usually present from birth or early life, but tends to go unrecognized. Data from 38 infants with non‐organic and 22 infants with organic FTT demonstrated that early clinical symptoms of feeding impairment, and obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
42
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(47 citation statements)
references
References 27 publications
5
42
0
Order By: Relevance
“…However, our results did not reveal any differences in developmental factors as measured by the Bayley Scales (Bayley 1969). Some clinicians and researchers (for example, Ramsey et al 1993) have suggested that OMD might occur as an isolated neurological sign that only becomes apparent in some children when solids are introduced, requiring a more organized and mature feeding pattern. Such difficulties could affect the child's ability to achieve an adequate intake and presumably result in FTT.…”
Section: Global Developmental Delaymentioning
confidence: 37%
See 4 more Smart Citations
“…However, our results did not reveal any differences in developmental factors as measured by the Bayley Scales (Bayley 1969). Some clinicians and researchers (for example, Ramsey et al 1993) have suggested that OMD might occur as an isolated neurological sign that only becomes apparent in some children when solids are introduced, requiring a more organized and mature feeding pattern. Such difficulties could affect the child's ability to achieve an adequate intake and presumably result in FTT.…”
Section: Global Developmental Delaymentioning
confidence: 37%
“…Feeding is the first 'joint task' of the mother-infant relationship and any interruption of this delicate relationship, such as a 'difficult feeder' may place extra demands and stresses on both the child and mother and so affect interactional style. Ramsey et al (1993) found that almost half the mothers of children with FTT exhibited negative effect and interactions during feeding time and suggested that the early feeding impairments may trigger the development of maladaptive interactional patterns. Lindberg et al (1996) studied mother-child interaction when children refuse food and found that the more difficult the infant, the less responsive the mother was to the child's cues.…”
Section: Children With Normal Oral-motor Function With Fttmentioning
confidence: 99%
See 3 more Smart Citations